2014
DOI: 10.1186/preaccept-2066059439130185
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor binds half sites as a monomer and regulates specific target genes

Abstract: Background: Glucocorticoid receptor (GR) is a hormone-activated, DNA-binding transcriptional regulatory factor that controls inflammation, metabolism, stress responses, and other physiological processes. In vitro, GR binds as an inverted dimer to a motif consisting of two imperfectly palindromic 6 bp half sites separated by 3 bp spacers. In vivo, GR employs different patterns of functional surfaces of GR to regulate different target genes. The relationships between GR genomic binding and functional surface uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…However, the discovery of monomeric occupancy near transcriptionally active genes, and the ability of monomeric-binding sites to drive transcription in vitro, indicate an expanded transactivation mechanism incorporating GR monomers. In support of this, similar monomeric function has recently been described in vitro for human U2OS osteosarcoma cell lines carrying stably integrated GR alleles (Schiller et al 2014). Revision of the transrepression mechanism may also be in order to include binding of GR monomers to half sites.…”
Section: Discussionsupporting
confidence: 60%
“…However, the discovery of monomeric occupancy near transcriptionally active genes, and the ability of monomeric-binding sites to drive transcription in vitro, indicate an expanded transactivation mechanism incorporating GR monomers. In support of this, similar monomeric function has recently been described in vitro for human U2OS osteosarcoma cell lines carrying stably integrated GR alleles (Schiller et al 2014). Revision of the transrepression mechanism may also be in order to include binding of GR monomers to half sites.…”
Section: Discussionsupporting
confidence: 60%
“…However, two 5Ј-AGAACA half-sites were identified in the XIRP1 promoter (at Ϫ560 and Ϫ64). HRE half-sites bound by GR monomers have also been implicated in GR trans-repression but not trans-activation (66). Therefore, the presence of these sites in the XIRP1 promoter seems like an unlikely explanation for the MR-dependent induction of XIRP1 as observed here.…”
Section: Discussionmentioning
confidence: 56%
“…Recent genome-wide ChIP-Seq analysis and ChIP exo Seq analysis demonstrated that the GR monomer binds to half GRE-like sites (Schiller et al, 2014;Lim et al, 2015;Starick et al, 2015). The half site motifs are in vicinity of binding to motifs of lineage-specific TFs observed in distinct cell lines and in liver and macrophages (Lim et al, 2015;Starick et al, 2015) ( Figure 1A).…”
Section: Transactivation and Transrepression Of Gene Regulation By Thmentioning
confidence: 95%